Membrane Electrode Assembly
By using proton conductive polymers containing cyclic ethers and sulfuric acid functional groups in the catalytic layer of solid polymer fuel cells, and adding fluoride pore reinforcement materials to the membrane electrodes, the problem of catalytic layer cracks is solved, and the durability and performance of the battery are improved.
Patent Information
- Application Number
- JP2024000109
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-13
- Filing Date
- 2024-01-04
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2040-03-12
AI Technical Summary
In the membrane electrode assembly of existing solid polymer fuel cells, cracks are prone to occur in the catalytic layer, which affects the durability of the battery.
A proton conductive polymer containing a cyclic ether structure and a sulfuric acid functional group is used in the catalytic layer, and a pore containing fluoride is added to the polymer electrolyte membrane as a reinforcement material to reduce stress differences.
It effectively reduces the occurrence of cracks in the catalytic layer, improves the durability of the membrane electrode assembly and the overall performance of the battery.
Smart Images

Figure 0007657405000031 
Figure 0007657405000001 
Figure 0007657405000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a membrane electrode assembly. [Background technology]
[0002] It is known that a membrane electrode assembly in a solid polymer fuel cell has an anode having a catalyst layer containing a proton-conducting polymer, a cathode having a catalyst layer containing a proton-conducting polymer, and a solid polymer electrolyte membrane disposed between the anode and the cathode. Patent Document 1 discloses the use of a proton-conducting polymer containing a unit having a cyclic ether structure in the catalyst layer of the anode or cathode. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 104380 Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, since solid polymer fuel cells are sometimes used for long periods of time, there is a demand for further improvement in the durability of the membrane electrode assemblies contained therein. The present inventors have found that when a proton-conductive polymer containing a unit having a cyclic ether structure as described in Patent Document 1 is used in a catalyst layer, cracks may occur in the catalyst layer.
[0005] In view of the above-mentioned circumstances, an object of the present invention is to provide a membrane electrode assembly capable of suppressing cracking of a catalyst layer. [Means for solving the problem]
[0006] As a result of intensive investigations into the above-mentioned problems, the present inventors have found that when a proton-conducting polymer contained in at least one of the catalyst layers of the anode and the cathode has a unit containing a cyclic ether structure and has a sulfonic acid type functional group, cracking of the catalyst layer can be suppressed by using a solid polymer electrolyte membrane containing a porous body containing a fluoropolymer and a fluoropolymer having a sulfonic acid type functional group, and have arrived at the present invention.
[0007] That is, the inventors discovered that the above problems can be solved by the following configuration. [1] A membrane electrode assembly comprising: an anode having a catalyst layer containing a proton-conducting polymer and a catalyst; a cathode having a catalyst layer containing a proton-conducting polymer and a catalyst; and a solid polymer electrolyte membrane disposed between the anode and the cathode, the proton-conducting polymer contained in the catalyst layer of at least one of the anode and the cathode is a polymer (H) having a unit containing a cyclic ether structure and having a sulfonic acid type functional group, A membrane / electrode assembly, characterized in that the solid polymer electrolyte membrane comprises a porous body containing a fluoropolymer, and a fluoropolymer (S) having a sulfonic acid type functional group. [2] The membrane / electrode assembly according to [1], wherein the unit having a cyclic ether structure includes at least one unit selected from the group consisting of a unit represented by formula (u12) described below and a unit represented by formula (u22) described below. [3] The membrane / electrode assembly according to [1] or [2], wherein the content of the unit having a cyclic ether structure is 30 mol % or more based on all units contained in the polymer (H). [4] The membrane / electrode assembly according to any one of [1] to [3], wherein the polymer (H) has an ion exchange capacity of 0.9 to 1.8 meq / g dry resin. [5] The membrane / electrode assembly according to any one of [1] to [4], wherein the precursor polymer (H) is a polymer in which the sulfonic acid functional group in the polymer (H) is a group that can be converted into a sulfonic acid group, and the TQ value of the precursor polymer (H) is 200 to 300° C. TQ value: When the precursor polymer (H) was melt-extruded using a nozzle having a length of 1 mm and an inner diameter of 1 mm under an extrusion pressure of 2.94 MPa, the extrusion amount was 100 mm 3 / sec. [6] The membrane / electrode assembly according to any one of [1] to [5], wherein the fluoropolymer (S) has at least one unit selected from the group consisting of a unit represented by the formula (u31) described later, a unit represented by the formula (u32) described later and a unit represented by the formula (u41) described later. [7] The membrane / electrode assembly according to any one of [1] to [6], wherein the ion exchange capacity of the fluoropolymer (S) is from 0.9 to 2.5 milliequivalents / g of dry resin. [8] The membrane / electrode assembly according to any one of [1] to [7], wherein the precursor polymer (S), which is a polymer in which the sulfonic acid type functional group in the fluoropolymer (S) is a group that can be converted into a sulfonic acid type group, has a TQ value of 200 to 350° C. TQ value: When the precursor polymer (S) was melt-extruded using a nozzle having a length of 1 mm and an inner diameter of 1 mm under an extrusion pressure of 2.94 MPa, the extrusion amount was 100 mm 3 / sec. [9] The membrane / electrode assembly according to any one of [1] to [8], wherein the porous body is in the form of a woven fabric, a nonwoven fabric, a foam or a film.
[10] The membrane / electrode assembly according to any one of [1] to [9], wherein the fluorine-containing polymer contained in the porous body is at least one selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, and tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer.
[11] The membrane / electrode assembly according to any one of [1] to
[10] , wherein the average pore size of the porous body is 0.01 to 500 μm.
[12] The membrane / electrode assembly according to any one of [1] to
[11] , wherein the porous body has an average thickness of 1 to 300 μm.
[13] The membrane / electrode assembly according to any one of [1] to
[12] , wherein the polymer (H) has a unit based on a perfluoromonomer and / or a unit based on tetrafluoroethylene (TFE).
[14] The membrane / electrode assembly according to any one of [1] to
[13] , wherein the polymer (S) has a unit based on a perfluoromonomer and / or a unit based on tetrafluoroethylene (TFE).
[15] The membrane / electrode assembly according to any one of [1] to
[14] , for use in a polymer electrolyte fuel cell. Effect of the Invention
[0008] According to the present invention, it is possible to provide a membrane electrode assembly capable of suppressing cracking of the catalyst layer. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view showing an example of a membrane electrode assembly of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The terms used in the present invention have the following meanings. A "unit" in a polymer means an atomic group derived from one molecule of a monomer formed by polymerization of the monomer. The unit may be an atomic group formed directly by a polymerization reaction, or may be an atomic group in which a part of the atomic group is converted into a different structure by treating the polymer obtained by the polymerization reaction. The content (mol %) of each unit relative to the total units contained in the polymer is determined by analyzing the polymer by nuclear magnetic resonance spectroscopy. A "sulfonic acid functional group" is a sulfonic acid group (-SO3H) or a sulfonate group (-SO3M 2 However, M 2 is an alkali metal or quaternary ammonium cation. The term "precursor group" refers to a group that can be converted into a sulfonic acid group by hydrolysis, acidification, salt exchange with a metal cation, or other treatment. The term "precursor polymer" refers to a polymer in which a sulfonic acid functional group is in the form of a precursor group and which can be converted into a polymer having a sulfonic acid functional group. A numerical range expressed using "~" means that the range includes the numerical values before and after "~" as the lower and upper limits.
[0011] The unit represented by the formula (u11) is written as unit (u11). The units represented by other formulas are written in the same way. Moreover, the monomer represented by the formula (m11) will be referred to as the monomer (m11). The monomers represented by the other formulae will be referred to in the same manner. In addition, the group represented by formula (g1) will be referred to as group (g1). Groups represented by other formulae will be similarly referred to.
[0012] The membrane electrode assembly of the present invention is a membrane electrode assembly having an anode having a catalyst layer containing a proton conducting polymer and a catalyst, a cathode having a catalyst layer containing a proton conducting polymer and a catalyst, and a solid polymer electrolyte membrane disposed between the anode and the cathode. The proton-conducting polymer contained in the catalyst layer of at least one of the anode and the cathode has a unit containing a cyclic ether structure (hereinafter also referred to as a "cyclic ether structural unit") and is a polymer (H) having a sulfonic acid type functional group. The solid polymer electrolyte membrane comprises a porous body containing a fluoropolymer, and a fluoropolymer (S) having a sulfonic acid functional group (hereinafter also referred to as "polymer (S)"). The membrane / electrode assembly of the present invention is suitably used for a solid polymer electrolyte fuel cell. According to the membrane electrode assembly of the present invention, cracks in the catalyst layer can be reduced. Although the details of the reason for this are not clear, it is presumed to be due to the following reasons.
[0013] A catalyst layer containing a polymer (H) having a cyclic ether structural unit tends to be harder than a catalyst layer containing a non-cyclic structural unit, and therefore the catalyst layer may crack due to the stress difference between the solid polymer electrolyte membrane and the catalyst layer containing the polymer (H). Regarding such a problem, when the solid polymer electrolyte membrane has a porous body containing a fluoropolymer, it is presumed that the porous body functions as a reinforcing material to alleviate the above-mentioned stress difference, thereby suppressing the occurrence of cracks in the catalyst layer.
[0014] 1 is a cross-sectional view showing an example of a membrane electrode assembly of the present invention. The membrane electrode assembly 10 has an anode 13 having a catalyst layer 11 and a gas diffusion layer 12, a cathode 14 having the catalyst layer 11 and the gas diffusion layer 12, and a solid polymer electrolyte membrane 15 disposed between the anode 13 and the cathode 14 in contact with the catalyst layer 11. In the following description, the anode and the cathode may be collectively referred to as "electrodes".
[0015] [Electrodes (anode and cathode)] The anode 13 and the cathode 14 each have a catalyst layer 11 and a gas diffusion layer 12 .
[0016] <Catalyst layer> The proton-conductive polymer contained in at least one of the catalyst layer 11 of the anode 13 and the catalyst layer 11 of the cathode 14 may be polymer (H), and both may be polymer (H). When the proton-conductive polymer contained in one catalyst layer 11 is polymer (H) and the proton-conductive polymer contained in the other catalyst layer 11 is not polymer (H), the proton-conductive polymer contained in the latter catalyst layer 11 is preferably polymer (S) described below. In the membrane / electrode assembly of the present invention, from the viewpoint of gas permeability, it is preferable that at least the proton-conducting polymer contained in the cathode is polymer (H).
[0017] The thickness of the catalyst layer is preferably from 1 to 20 μm, particularly preferably from 3 to 10 μm, from the viewpoints of facilitating gas diffusion in the catalyst layer and improving the power generation performance of the polymer electrolyte fuel cell. The thickness of the catalyst layer is measured by observing the cross section of the catalyst layer with a scanning electron microscope or the like.
[0018] (Polymer (H)) The polymer (H) is a polymer having a cyclic ether structural unit and a sulfonic acid type functional group. The cyclic ether structural unit preferably contains at least one unit selected from the group consisting of units (u11), (u12), (u13), (u22) and (u24), since a catalyst layer having better oxygen permeability can be obtained, more preferably units (u12) and (u22), and particularly preferably unit (u22).
[0019] [ka]
[0020] R 11 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 17 SO2X(SO2R f ) a - M + It is a group represented by the following formula: The monovalent perfluoro organic group is preferably a perfluoroalkyl group. When the perfluoroalkyl group has an ether bond oxygen atom, the number of oxygen atoms may be one or more. In addition, the oxygen atom may be located between the carbon-carbon bonds of the perfluoroalkyl group, or may be located at the carbon atom bond end. The perfluoroalkyl group may be linear or branched, but is preferably linear. R 17is a divalent perfluoro organic group which may have an ether bond oxygen atom. The organic group is a group having one or more carbon atoms. The divalent perfluoro organic group is preferably a perfluoroalkylene group. When the perfluoroalkylene group has an ether bond oxygen atom, the number of oxygen atoms may be one or more. In addition, the oxygen atom may be located between the carbon-carbon bonds of the perfluoroalkylene group, or may be located at the carbon atom bond end. The perfluoroalkylene group may be linear or branched, but is preferably linear. M + is H + , a monovalent metal cation (e.g., potassium ion, sodium ion) or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group (e.g., methyl group, ethyl group). From the viewpoint of high conductivity, H + is preferred. R f is a straight-chain or branched perfluoroalkyl group which may have an ether-bonded oxygen atom. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 8, and more preferably 1 to 6. Two or more R f If there are two or more R f may be the same or different from each other. X is an oxygen atom, a nitrogen atom, or a carbon atom. When X is an oxygen atom, (SO2R f ) a In the formula, a is 0, and when X is a nitrogen atom, (SO2R f ) a In the formula, a is 1, and when X is a carbon atom, (SO2R f ) a In this case, a is 2. -(SO2X(SO2R f ) a ) - M + Specific examples of groups include sulfonic acid groups (-SO3 - M + group), sulfonimide group (-SO2N(SO2R f ) - M +group), or sulfonmethide group (-SO2C(SO2R f )2) - M + Groups such as R 12 , R 13 , R 15 and R 16 are each independently a monovalent perfluoro organic group which may have an ether-bonded oxygen atom or a fluorine atom. As the monovalent perfluoro organic group, a perfluoroalkyl group is preferable. 15 and R 16 From the viewpoint of high polymerization reactivity, it is preferable that at least one of them is a fluorine atom, and it is particularly preferable that both of them are fluorine atoms. R 14 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 17 SO2X(SO2R f ) a - M + The monovalent perfluoro organic group is preferably a perfluoroalkyl group. When the perfluoroalkyl group has an ether-bonded oxygen atom, the number of oxygen atoms may be one or more. The oxygen atom may be located between the carbon-carbon bonds of the perfluoroalkyl group, or may be located at the carbon atom bond end. The perfluoroalkyl group may be linear or branched, but is preferably linear. In formula (u11), two or more R 17 , X 、 R f , a, and M + If it contains more than one R 17 , X 、 R f , a, and M + may be the same or different from each other.
[0021] The unit (u11) is preferably the unit (u11-1) or the unit (u11-2).
[0022] [ka]
[0023] [ka]
[0024] R 21 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and having an ether-bonding oxygen atom between the carbon-carbon bonds. When the perfluoroalkylene group has an ether-bonding oxygen atom, the number of oxygen atoms may be 1 or 2 or more. The perfluoroalkylene group may be linear or branched, but is preferably linear. R 22 is a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, or -R 21 (SO2X(SO2R f ) a ) - M + In the case where the perfluoroalkyl group has an ether-bonded oxygen atom, the number of oxygen atoms may be one or more. The perfluoroalkyl group may be linear or branched, but is preferably linear. In the formula (u12), two R 21 If it contains two R 21 may be the same or different from each other. M + , R f , X and a are the M + , R f , X and a.
[0025] Specific examples of the unit (u12) include the unit (u12-1) and the unit (u12-2). + is M in equation (u11). + is synonymous with.
[0026] [ka]
[0027] [ka]
[0028] R 31 represents a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, -R 37 SO2X(SO2R f ) a - M + It is a group represented by the following formula: When the perfluoroalkyl group has an ether-bonded oxygen atom, the number of oxygen atoms may be 1 or 2 or more. The perfluoroalkyl group may be linear or branched, but is preferably linear. R 37 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and having an ether-bonding oxygen atom between the carbon-carbon bonds. When the perfluoroalkylene group has an ether-bonding oxygen atom, the number of oxygen atoms may be 1 or 2 or more. The perfluoroalkylene group may be linear or branched, but is preferably linear. R 32 ~R 35 are each independently a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, or a perfluoroalkyl group having 2 to 6 carbon atoms and having an ether-bonding oxygen atom between the carbon-carbon bond. When the perfluoroalkyl group has an ether-bonding oxygen atom, the number of oxygen atoms may be 1 or 2 or more. The perfluoroalkyl group may be linear or branched, but is preferably linear. R 36is a single bond, a perfluoroalkylene group having 1 to 6 carbon atoms, or a perfluoroalkylene group having 2 to 6 carbon atoms and having an ether-bonding oxygen atom between the carbon-carbon bond. When the perfluoroalkylene group has an ether-bonding oxygen atom, the number of oxygen atoms may be 1 or 2 or more. The perfluoroalkylene group may be linear or branched, but is preferably linear. M + , R f , X and a are the M + , R f , X and a.
[0029] [ka]
[0030] s is 0 or 1, with 0 being preferred. R 51 and R 52 each independently represents a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a spiro ring formed by linking together (with the proviso that s is 0). R 53 and R 54 each independently represents a fluorine atom or a perfluoroalkyl group having 1 to 5 carbon atoms. R 55 R is a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. 55 is preferably a fluorine atom because of its high polymerization reactivity. The perfluoroalkyl group and the perfluoroalkoxy group may be linear or branched, but are preferably linear.
[0031] The unit (u22) is preferably the unit (u22-1).
[0032] [ka]
[0033] [ka]
[0034] R 71 ~R 76 are each independently a monovalent perfluoro organic group which may have an ether-bonding oxygen atom or a fluorine atom. The monovalent perfluoro organic group is preferably a perfluoroalkyl group. When the perfluoroalkyl group has an ether-bonding oxygen atom, the number of oxygen atoms may be one or more. In addition, the oxygen atom may be inserted between the carbon-carbon bond of the perfluoroalkyl group, or may be inserted at the carbon atom bond end. The perfluoroalkyl group may be linear or branched, but is preferably linear. R 71 ~R 74 is preferably a fluorine atom because of its high polymerization reactivity.
[0035] The content of the cyclic ether structural unit relative to all units contained in the polymer (H) is preferably 30 mol % or more, more preferably 40 mol % or more, even more preferably 50 mol % or more, and particularly preferably 70 mol % or more, in view of better power generation efficiency of the fuel cell. The upper limit of the content of the cyclic ether structural unit is preferably 100 mol %, particularly preferably 80 mol %, based on all units contained in the polymer (H). The polymer (H) may contain only one type of specific cyclic ether structural unit, or may contain two or more types. When two or more types are contained, the above content means the total amount thereof.
[0036] The polymer (H) may further contain a unit based on a perfluoromonomer, provided that the unit based on the perfluoromonomer does not contain a cyclic ether structure and contains a unit having a sulfonic acid type functional group. Examples of the unit based on a perfluoromonomer include the unit (u31), the unit (u32) and the unit (u41). From the viewpoint of achieving superior power generation efficiency of the fuel cell, the unit (u32) and the unit (u41) are preferred.
[0037] [ka]
[0038] Z is a fluorine atom or a trifluoromethyl group, q is 0 or 1, m is an integer of 0 to 3, p is 0 or 1, n is an integer of 1 to 12, and m+p>0. M + is the M in the above formula (u11). + is synonymous with.
[0039] [ka]
[0040] Q 1 is a perfluoroalkylene group which may have an ether-bonding oxygen atom. Q 2 is a single bond or a perfluoroalkylene group which may have an ether-bonded oxygen atom. Q 1 and Q 2 When the perfluoroalkylene group has an ether-bonding oxygen atom, the number of oxygen atoms may be 1 or 2 or more. In addition, the oxygen atom may be located between the carbon atom-carbon atom bonds of the perfluoroalkylene group, or may be located at the end of the carbon atom bond. The perfluoroalkylene group may be linear or branched, but is preferably linear. The carbon number of the perfluoroalkylene group is preferably 1 to 6, particularly preferably 1 to 4. When the carbon number is 6 or less, the boiling point of the raw material fluorine-containing monomer is low, and distillation purification is easy. In addition, when the carbon number is 6 or less, the decrease in the ion exchange capacity of the polymer (H) is suppressed, and the proton conductivity is good.
[0041] Q 2 is preferably a perfluoroalkylene group having 1 to 6 carbon atoms which may have an ether-bonding oxygen atom. 2 is a perfluoroalkylene group having 1 to 6 carbon atoms which may have an ether-bonding oxygen atom, 2 is a single bond, the stability of power generation performance is excellent when the fuel cell is operated for a long period of time. Q 1 and Q 2 At least one of the groups is preferably a perfluoroalkylene group having 1 to 6 carbon atoms and an ethereal oxygen atom. A monomer having a perfluoroalkylene group having 1 to 6 carbon atoms and an ethereal oxygen atom can be synthesized without going through a fluorination reaction with fluorine gas, and therefore the yield is good and the production is easy.
[0042] Y is a fluorine atom or a monovalent perfluoro organic group. Y is preferably a fluorine atom or a linear perfluoroalkyl group having 1 to 6 carbon atoms which may have an etheric oxygen atom. q is 0 or 1. R f , X and a are R in the above formula (u11), f , X and a are synonymous. Two or more R f , a and X, two or more R f , a and X may be the same or different.
[0043] As the unit (u32), the units (u32-1) to (u32-3) are preferred, and the unit (u32-1) is particularly preferred, since they are easy to produce and easy to implement industrially.
[0044] [ka]
[0045] [ka]
[0046] R F1 and R F2 each independently represents a perfluoroalkylene group having 1 to 3 carbon atoms. R F1 and R F2 Specific examples of R include -CF2-, -CF2CF2-, -CF(CF3)-, -CF2CF2CF2-, -CF(CF2CF3)-, -CF(CF3)CF2-, -CF2CF(CF3)-, and -C(CF3)(CF3)-. R is more preferred because it is cheaper to manufacture and easier to produce, and it can have a higher ion exchange capacity. F1 and R F2 is preferably a group having 1 to 2 carbon atoms and is preferably linear. Specifically, -CF2-, -CF2CF2- or -CF(CF3)- is preferred, with -CF2- being particularly preferred. Z + is H + , a monovalent metal cation (e.g., potassium ion, sodium ion) or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group (e.g., methyl group, ethyl group). From the viewpoint of high conductivity, H + is preferred. + may be the same or different from each other.
[0047] The content of the units based on the perfluoromonomer is preferably from 5 to 40 mol %, more preferably from 10 to 35 mol %, and particularly preferably from 15 to 30 mol %, based on all the units contained in the polymer (H). The polymer (H) may contain only one type of unit based on a perfluoromonomer, or may contain two or more types. When two or more types are contained, the above content means the total amount thereof.
[0048] The polymer (H) may further contain units based on tetrafluoroethylene (TFE), which imparts water repellency and increases the water discharge ability in the catalyst layer, thereby improving the power generation efficiency of the fuel cell. The content of units based on tetrafluoroethylene is preferably from 0 to 40 mol %, more preferably from 5 to 35 mol %, and particularly preferably from 5 to 30 mol %, based on all units contained in the polymer (H).
[0049] The polymer (H) may contain units other than those mentioned above (hereinafter, also referred to as "other units"). Specific examples of such units include units based on monomers such as perfluoro(3-butenyl vinyl ether), perfluoro(allyl vinyl ether), perfluoro α-olefins (hexafluoropropylene, etc.), and perfluoro(alkyl vinyl ethers).
[0050] A preferred embodiment of the polymer (H) is one containing units (u22) since this provides better power generation efficiency in a fuel cell. A more preferred embodiment of the polymer (H) is one containing the unit (u22) and at least one of the unit (u11) and the unit (u12), because this provides particularly excellent power generation efficiency in a fuel cell. Another more preferred embodiment of the polymer (H) is an embodiment containing units (u22), units based on a perfluoromonomer, and units based on tetrafluoroethylene, from the viewpoint of particularly excellent power generation efficiency of a fuel cell.
[0051] The ion exchange capacity of the polymer (H) is preferably from 0.9 to 1.8 milliequivalents / g dry resin, more preferably from 1.0 to 1.7 milliequivalents / g dry resin, particularly preferably from 1.0 to 1.6 milliequivalents / g dry resin. If the ion exchange capacity is equal to or greater than the lower limit of the above range, the ion conductivity of the polymer (H) is high, so that sufficient cell output can be obtained when the membrane electrode assembly is applied to a polymer electrolyte fuel cell. If the ion exchange capacity is equal to or less than the upper limit of the above range, flooding of the polymer electrolyte fuel cell can be suppressed when the membrane electrode assembly is applied to a polymer electrolyte fuel cell. The ion exchange capacity of the polymer (H) can be determined by the method described in the Examples section below.
[0052] The TQ value (volumetric flow rate value) of the precursor polymer (H) of the polymer (H) is preferably from 200 to 300°C, more preferably from 220 to 300°C, and particularly preferably from 240 to 290°C. When the TQ value is equal to or greater than the lower limit of the above range, the polymer (H) has a sufficient molecular weight and is excellent in mechanical strength. When the TQ value is equal to or less than the upper limit of the above range, the solubility or dispersibility of the polymer (H) is improved, so that a liquid composition containing the polymer (H) can be easily prepared. The TQ value is an index of the molecular weight of the polymer (H). The TQ value of the precursor polymer (H) is measured by the method described in the Examples section below.
[0053] (Method for producing polymer (H)) The polymer (H) is produced, for example, by converting a precursor group of a polymer having a precursor group of a sulfonic acid type functional group obtained by polymerizing at least a specific cyclic monomer into a sulfonic acid type functional group. Each monomer that can be used in the production of the polymer (H) will be described below.
[0054] The unit (u11) is obtained by polymerizing the monomer (m11), and preferred embodiments of the monomer (m11) include the monomers (m11-1) to (m11-6). The monomer (m11) can be synthesized by a known method. In formula (m11), R 110 represents a monovalent perfluoro organic group which may have an ether-bonded oxygen atom, a fluorine atom, or -R 17 It is a group represented by SO2F. R 17 is R in formula (u11) 17 is synonymous with. R in formula (m11) 12 ~R 16 are the R in equation (u11), 11 ~R 16 is synonymous with.
[0055] [ka]
[0056] The unit (u12) is obtained by polymerizing the monomer (m12), and preferred embodiments of the monomer (m12) include the monomers (m12-1) and (m12-2). The monomer (m12) can be synthesized by a known method. R in formula (m12) 21 and R 22 R in formula (u12) 21 ~R 22 is synonymous with.
[0057] [ka]
[0058] The unit (u13) is obtained by polymerizing the monomer (m13), and preferred embodiments of the monomer (m13) include the monomers (m13-1) to (m13-4). The monomer (m13) can be synthesized by a known method. R in formula (m13) 310 represents a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and an ether-bonded oxygen atom between the carbon-carbon bonds, -R 37 It is a group represented by SO2F. R 37 is R in formula (u13). 37 is synonymous with. R in formula (m13) 32 ~R 36 R in equation (u13) 32 ~R 36 is synonymous with.
[0059] [ka]
[0060] The unit (u22) is obtained by polymerizing the monomer (m22), and preferred embodiments of the monomer (m22) include the monomers (m22-1) and (m22-11). The monomer (m22) can be synthesized by a known method. R in formula (m22) 51~R 55 and s are R in formula (u22), 51 ~R 55 and s.
[0061] [ka]
[0062] The unit (u24) is obtained by cyclopolymerizing the monomer (m24), and preferred embodiments of the monomer (m24) include the monomers (m24-1) to (m24-3). The monomer (m24) can be synthesized by a known method.
[0063] CF(R 71 )=C(R 73 )-O-CF(R 76 )-CF(R 75 )-C(R 74 )=CF(R 72 ) (m24) CF2=CF-O-CF2-CF2-CF=CF2(m24-1) CF2=CF-O-CF2-CF(CF3)-CF=CF2(m24-2) CF2=CF-O-CF(CF3)-CF2-CF=CF2(m24-3)
[0064] For the production of the polymer (H), a perfluoromonomer that does not contain a cyclic ether structure and contains a precursor group of a sulfonic acid type functional group may be used. Examples of the perfluoromonomer include the monomer (m31), the monomer (m32) and the monomer (m41). From the viewpoint of achieving superior power generation efficiency in the fuel cell, the monomer (m32) and the monomer (m41) are preferred.
[0065] CF2=CF(CF2) q (OCF2CFZ) m O p (CF2) n SO2F (m31)
[0066] The monomer (m31) corresponds to the unit (u31). Z, q, m, p and n have the same meanings as Z, q, m, p and n in formula (u31), respectively.
[0067] The monomer (m31) is preferably the monomers (m31-1) to (m31-3). CF2 = CFO(CF2) n1 SO2F (m31-1) CF2 = CFOCF2CF(CF3)O(CF2) n2 SO2F (m31-2) CF2=CF(OCF2CF(CF3)) m3 O(CF2) n3 SO2F (m31-3) CF2 = CFCF2O(CF2) n4 SO2F (m31-4) Here, n1, n2, n3, and n4 are integers from 1 to 8, and m3 is an integer from 1 to 3.
[0068] The monomer (m31) can be synthesized, for example, by the method described in Prog. Polym. Sci., Vol. 12, 1986, p. 233-237; US Pat. No. 4,330,654, and the like.
[0069] [ka]
[0070] Q 1 , Q 2 , Y and q are the Q 1 , Q 2 , Y and q.
[0071] The monomer (m32) corresponds to the unit (u32). As the monomer (m32), the polymer (H) can be easily produced and the production can be easily carried out industrially. Therefore, the monomers (m32-1) to (m32-3) are preferred, and the monomer (m32-1) is particularly preferred.
[0072] [ka]
[0073] The monomer (m32) can be synthesized, for example, by the method described in WO 2007 / 013533, JP 2008-202039 A, and the like.
[0074] [ka]
[0075] The monomer (m41) corresponds to the unit (u41). R F1 and R F2 are R in equation (u41), F1 and R F2 is synonymous with. A specific example of the monomer (m41) is the monomer (m41-1).
[0076] [ka]
[0077] The monomer (m41) can be produced, for example, by the method described in the Examples section below.
[0078] Tetrafluoroethylene may be used in the production of polymer (H).
[0079] Monomers other than those mentioned above may be used in the production of polymer (H). Specific examples of such monomers include perfluoro(3-butenyl vinyl ether), perfluoro(allyl vinyl ether), perfluoro α-olefins (such as hexafluoropropylene), and perfluoro(alkyl vinyl ethers).
[0080] The precursor group (-SO2F) can be converted to a sulfonic acid functional group by a known method.
[0081] The polymer (H) in which the sulfonic acid functional group is a sulfonimide group can also be produced by polymerizing a monomer in which the group represented by -SO2F in the monomer (m11), (m12), (m13), (m31), (m32) or (m41) has been converted to a sulfonimide group, together with the monomer (m24). A monomer in which the group represented by -SO2F has been converted into a sulfonimide group can be produced by adding chlorine or bromine to the carbon-carbon double bond of monomer (m11), (m12), (m13), (m32) or (m41) to convert the group represented by -SO2F into a sulfonimide group, followed by a dechlorination or debromination reaction using metallic zinc.
[0082] (catalyst) The catalyst contained in the catalyst layer may be, for example, a supported catalyst in which platinum or a platinum alloy is supported on a carbon support. Specific examples of the carbon support include carbon black powder, graphitized carbon, carbon fiber, and carbon nanotubes. The platinum alloy is preferably an alloy of platinum with at least one metal selected from the group consisting of platinum group metals excluding platinum (ruthenium, rhodium, palladium, osmium, iridium), gold, silver, chromium, iron, titanium, manganese, cobalt, nickel, molybdenum, tungsten, aluminum, silicon, zinc, and tin. When a supported catalyst is used, the amount of the catalyst supported is preferably 10 to 80 mass %, particularly preferably 10 to 70 mass %, based on the total mass of the supported catalyst, from the standpoint of superior power generation efficiency of the fuel cell and cost. When a supported catalyst is used, the ratio of the mass of polymer (H) to the mass of the support (polymer (H) content / support content) is preferably 0.5 to 2.0, particularly preferably 0.6 to 1.8, in terms of excellent power generation efficiency of the fuel cell.
[0083] <Gas diffusion layer> The gas diffusion layer 12 has a function of diffusing gas uniformly in the catalyst layer 11 and also functions as a current collector. Examples of the gas diffusion layer 12 include carbon paper, carbon cloth, carbon felt, etc. The gas diffusion layer 12 is preferably treated with polytetrafluoroethylene or the like to be water repellent. Although the membrane electrode assembly 10 in FIG. 1 includes a gas diffusion layer 12, the gas diffusion layer is an optional member and does not necessarily have to be included in the membrane electrode assembly.
[0084] <Other materials> The anode 13 and the cathode 14 may include other components in addition to those described above. A specific example of the other member is a carbon layer (not shown) provided between the catalyst layer 11 and the gas diffusion layer 12. By providing the carbon layer, the gas diffusion property of the surface of the catalyst layer 11 is improved, and the power generation performance of the fuel cell can be further improved. The carbon layer contains, for example, carbon and a non-ionic fluorine-containing polymer. A specific example of the carbon is preferably carbon nanofiber having a fiber diameter of 1 to 1000 nm and a fiber length of 1000 μm or less. A specific example of the non-ionic fluorine-containing polymer is polytetrafluoroethylene.
[0085] <Method of forming catalyst layer> The catalyst layer 11 can be formed by a known method.
[0086] [Solid polymer electrolyte membrane] The solid polymer electrolyte membrane 15 is a membrane containing a porous body containing a fluoropolymer and a polymer (S).
[0087] The thickness of the solid polymer electrolyte membrane is preferably from 1 to 200 μm, particularly preferably from 5 to 100 μm. The thickness of the solid polymer electrolyte membrane is measured by observing a cross section of the solid polymer electrolyte membrane with a scanning electron microscope or the like.
[0088] <Porous body> The porous body means a member having a large number of pores in the thickness direction. The pores preferably penetrate the member in the thickness direction. The form of the porous body is preferably in the form of a sheet, and specific examples include woven fabric, nonwoven fabric, foam and film. Among these, a film (porous film) is preferred because it provides better effects of the present invention, and a film in which holes are formed by a stretching method is particularly preferred. The porous body is, for example, contained on the surface or inside of the solid polymer electrolyte membrane.
[0089] The porous body contains a fluoropolymer. The fluoropolymer means a polymer having fluorine atoms. Specific examples of the fluorine-containing polymer include polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, and tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer. Among these, polytetrafluoroethylene is preferred in terms of the superior effect of the present invention and mechanical and chemical durability. The porous body may contain only one type of fluorine-containing polymer, or may contain two or more types.
[0090] The porous body may be a commercially available product, for example, Tetratex II 3108 (manufactured by Donaldson Co.).
[0091] The average pore size of the porous body is preferably 0.01 to 500 μm, particularly preferably 0.05 to 250 μm. When the average pore size of the porous body is equal to or larger than the lower limit, the performance of the membrane electrode assembly can be maintained at a good level. When the average pore size of the porous body is equal to or smaller than the upper limit, the strength of the porous body is improved, and the stress difference between the solid polymer electrolyte membrane and the catalyst layer containing the polymer (H) can be further reduced, so that the occurrence of cracks in the catalyst layer can be further suppressed. The average pore size of the porous body can be measured by the bubble point method (JIS K3832).
[0092] The average thickness of the porous body is preferably from 1 to 300 μm, particularly preferably from 5 to 100 μm, from the viewpoint of further suppressing the occurrence of cracks in the catalyst layer while maintaining the performance of the membrane / electrode assembly at a good level. The average thickness of the porous body is calculated as the arithmetic mean value of thickness measurements taken at any four locations using a Digimatic Indicator (Mitutoyo, 543-250, flat measuring probe: diameter 5 mm).
[0093] <Polymer (S)> The polymer (S) is a fluorine-containing polymer having a sulfonic acid type functional group contained in the solid polymer electrolyte membrane. The polymer (S) may be any polymer having a sulfonic acid functional group and a fluorine atom, but from the viewpoint of high chemical durability, it is preferable that the polymer (S) has units based on the above-mentioned perfluoromonomer that can be contained in the polymer (H). Specific examples of the unit based on a perfluoromonomer in the polymer (S) include the unit (u31), the unit (u32) and the unit (u41). From the viewpoint of achieving better power generation efficiency of the fuel cell, the unit (u32) and the unit (u41) are preferred, and the unit (u32) is particularly preferred.
[0094] The content of the units based on the perfluoromonomer is preferably from 5 to 40 mol %, more preferably from 10 to 35 mol %, and particularly preferably from 15 to 30 mol %, based on all the units contained in the polymer (S). The polymer (S) may contain only one type of unit based on a perfluoromonomer, or may contain two or more types. When two or more types are contained, the above content means the total amount thereof.
[0095] The polymer (S) may further comprise units based on tetrafluoroethylene (TFE). The content of units based on tetrafluoroethylene is preferably from 50 to 90 mol %, more preferably from 60 to 85 mol %, and particularly preferably from 65 to 80 mol %, based on all units contained in the polymer (S).
[0096] The polymer (S) may contain units other than those mentioned above (hereinafter, also referred to as "other units"). Specific examples of such units are the same as the other units in the polymer (H).
[0097] The ion exchange capacity of the polymer (S) is preferably from 0.9 to 2.5 milliequivalents / g dry resin, more preferably from 1.1 to 2.4 milliequivalents / g dry resin, particularly preferably from 1.2 to 2.3 milliequivalents / g dry resin. If the ion exchange capacity is equal to or greater than the lower limit of the above range, the ion conductivity of the polymer (S) is high, and therefore sufficient cell output can be obtained when the membrane electrode assembly is applied to a polymer electrolyte fuel cell. If the ion exchange capacity is equal to or less than the upper limit of the above range, swelling of the polymer (S) when it absorbs water is suppressed, and the mechanical strength of the solid polymer electrolyte membrane is increased. Flooding of the polymer electrolyte fuel cell can be suppressed. The ion exchange capacity of the polymer (S) can be determined by the method described in the Examples section below.
[0098] The TQ value of the precursor polymer (S) of the polymer (S) is preferably from 200 to 350°C, more preferably from 210 to 340°C, and particularly preferably from 220 to 330°C. When the TQ value is equal to or greater than the lower limit of the above range, the polymer (S) has a sufficient molecular weight and is excellent in mechanical strength. When the TQ value is equal to or less than the upper limit of the above range, the solubility or dispersibility of the polymer (S) is improved, so that a liquid composition containing the polymer (S) can be easily prepared. The TQ value of the precursor polymer (S) is measured by the method described in the Examples section below.
[0099] (Method for producing polymer (S)) The polymer (S) is produced, for example, by polymerizing a monomer having a precursor group (-SO2F group) of a sulfonic acid functional group, and converting the precursor group of the polymer obtained by this polymerization into a sulfonic acid functional group. Specific examples of monomers that can be used in the production of polymer (S) include monomer (m31), monomer (m32), monomer (m41), tetrafluoroethylene, perfluoro(3-butenyl vinyl ether), perfluoro(allyl vinyl ether), perfluoro α-olefins (hexafluoropropylene, etc.), and perfluoro(alkyl vinyl ethers) exemplified in the production method for polymer (H). The method for converting the precursor group of the sulfonic acid functional group into the sulfonic acid functional group is the same as in the production method of polymer (H).
[0100] <Other materials> In order to further improve durability, the solid polymer electrolyte membrane 15 may contain one or more atoms selected from the group consisting of cerium and manganese. Cerium and manganese decompose hydrogen peroxide, which is a substance that causes deterioration of the solid polymer electrolyte membrane 15. Cerium and manganese are preferably present as ions in the solid polymer electrolyte membrane 15, but may also be present as a sparingly soluble salt, such as cerium oxide. The solid polymer electrolyte membrane 15 may contain silica or heteropolyacid (zirconium phosphate, phosphomolybdic acid, phosphotungstic acid, etc.) as a water retention agent to prevent drying.
[0101] <Method of forming solid polymer electrolyte membrane> The solid polymer electrolyte membrane 15 can be formed, for example, by a method (casting method) in which a liquid composition containing the polymer (S) is applied onto the substrate film or catalyst layer 11 and dried. The liquid composition is a dispersion in which the polymer (S) is dispersed in a solvent containing at least one of an organic solvent and water.
[0102] [Method of manufacturing membrane electrode assembly] The membrane electrode assembly 10 is produced, for example, by the following method. (i) A method in which a catalyst layer 11 is formed on a solid polymer electrolyte membrane 15 to form a membrane catalyst layer assembly, and the membrane catalyst layer assembly is sandwiched between gas diffusion layers 12. (ii) A method in which a catalyst layer 11 is formed on a gas diffusion layer 12 to form electrodes (anode 13, cathode 14), and the solid polymer electrolyte membrane 15 is sandwiched between the electrodes. EXAMPLES
[0103] The present invention will be described in detail below with reference to examples. Examples 1 and 2 are working examples, and Example 3 is a comparative example. However, the present invention is not limited to these examples.
[0104] [Proportion of each unit] The proportion of each unit in the polymer is 19 It was determined from the results of F-NMR measurements.
[0105] [Ion exchange capacity] The ion exchange capacity of each polymer having a -SO3H group was determined by the following method. The polymer was placed in a glove box and left in an atmosphere of dry nitrogen for 24 hours or more to dry it. The dry mass of the polymer was measured in the glove box. The polymer was immersed in a 2 mol / L (liter) aqueous sodium chloride solution, left at 60°C for 1 hour, and then cooled to room temperature. The aqueous sodium chloride solution in which the polymer had been immersed was titrated with a 0.5 mol / L aqueous sodium hydroxide solution to determine the ion exchange capacity of the polymer.
[0106] [TQ value] Using a flow tester CFT-500A (Shimadzu Corporation) equipped with a nozzle with a length of 1 mm and an inner diameter of 1 mm, the extrusion amount of the precursor polymer was measured by changing the temperature under the condition of an extrusion pressure of 2.94 MPa. 3 The temperature at which the thermal expansion coefficient (TQ) reaches 1 / sec was calculated.
[0107] [Anode catalyst layer forming solution] 217.8 g of water and 178.2 g of ethanol were added to 44 g of a supported catalyst (Tanaka Kikinzoku Kogyo Co., Ltd., TEC10E50E) in which 46 mass % of platinum was supported on carbon powder, and the mixture was mixed and pulverized using an ultrasonic homogenizer to obtain a catalyst dispersion. A polymer (ion exchange capacity: 1.10 meq / g dry resin, TQ value of precursor polymer: 230°C) was copolymerized with TFE and a monomer (m31-2-1) in a catalyst dispersion and then hydrolyzed and acid-treated to form an acid form. The polymer was dispersed in a solvent of water / ethanol = 40 / 60 (mass%) at a solid content concentration of 25.8% (hereinafter also referred to as "dispersion X"). 80.16 g of this dispersion, 44.4 g of ethanol, and 25.32 g of Zeorola-H (manufactured by Zeon Corporation) were mixed and kneaded in advance, and 117.4 g of a mixed liquid was added, and 163.42 g of water and 139.12 g of ethanol were further added and mixed using an ultrasonic homogenizer to adjust the solid content concentration to 7 mass%, thereby obtaining a coating solution for forming an anode catalyst layer. CF2=CFOCF2CF(CF3)OCF2CF2SO2F (m31-2-1)
[0108] [Cathode catalyst layer forming solution] <Production of Polymer (H-1)> In a stainless steel autoclave with an internal volume of 230 mL, 133.16 g of monomer (m32-1), 32.67 g of monomer (m22-1), and 14.1 g of solvent (AGC, Asahiklin (registered trademark) AC-2000) were charged, and the mixture was thoroughly degassed under cooling with liquid nitrogen. 3.94 g of TFE (tetrafluoroethylene) was charged, the temperature was raised to 24°C, 40.17 mg of radical polymerization initiator ((C3F7COO)2) dissolved in a solvent (CClF2CF2CHClF) at a concentration of 2.8% by mass was charged, and the charging line was washed with 1.1 g of AC-2000 to start the reaction. After stirring for 8 hours, the autoclave was cooled to stop the reaction. The product was diluted with AC-2000, then mixed with a mixture of AC-2000:methanol = 8:2 (mass ratio) to flocculate the polymer and filter it. The polymer was washed in a mixture of AC-2000:methanol = 7:3 (mass ratio) and separated by filtration. The solid was dried under reduced pressure at 80°C overnight to obtain polymer (H'-1). The resulting polymer (H'-1) was immersed in an aqueous solution containing 20% by mass of methanol and 15% by mass of potassium hydroxide at 50°C for 40 hours, whereby the -SO2F groups in the polymer (H'-1) were hydrolyzed and converted to -SO3K groups. The polymer was then immersed in a 3 mol / L aqueous hydrochloric acid solution at room temperature for 2 hours. The aqueous hydrochloric acid solution was replaced, and the same treatment was repeated four more times to obtain a polymer (H-1) in which the -SO3K groups in the polymer were converted to sulfonic acid groups. The composition of the structural units constituting the polymer (H'-1) is 19 When analyzed by F-NMR, the content of units based on monomer (m22-1) in polymer (H-1) was 67 mol %, the content of units based on monomer (m32-1) was 18 mol %, and the content of units based on TFE was 15 mol %, relative to all units contained in polymer (H-1). The TQ value of the polymer (H'-1) was 275°C. The ion exchange capacity of the polymer (H-1) was determined to be 1.23 meq / g dry resin.
[0109] [ka]
[0110] [ka]
[0111] <Preparation of liquid for forming cathode catalyst layer> Polymer (H-1) and a mixed solvent of water and 1-propanol (water / 1-propanol = 50 / 50 mass ratio) were stirred in a Hastelloy autoclave at 115°C for 8 hours at a rotation speed of 150 rpm to prepare a dispersion with a polymer (H-1) concentration of 18 mass%. 49.5g of ultrapure water and 40.5g of ethanol were added to 10g of a catalyst (Tanaka Kikinzoku Kogyo Co., Ltd., TEC10E50E) in which platinum was supported on carbon powder to a content of 46% by mass, and ultrasonic waves were applied for 10 minutes to prepare a catalyst dispersion. 20.4g of the dispersion of polymer (H-1) was added to this, and the mass ratio of polymer (H-1) to catalyst carbon (polymer (H-1) mass / catalyst carbon mass) was set to 0.8, and 20.8g of ultrapure water and 29.8g of ethanol were further added to adjust the solid content concentration to 8% by mass, to obtain a cathode catalyst layer forming liquid.
[0112] [Solid polymer electrolyte membrane 1] CF2=CF2 and the above monomer (m32-1) were copolymerized to obtain a polymer (S'-1) (ion exchange capacity: 1.95 meq / g dry resin, TQ value: 236°C). The polymer (S'-1) was molded by melt extrusion to obtain a membrane (thickness: 200 µm) made of the polymer (S'-1). The ion exchange capacity shown in parentheses for polymer (S'-1) represents the ion exchange capacity of the polymer obtained when hydrolyzed by the procedure described below. The membrane was immersed in an aqueous solution containing 20% by mass of potassium hydroxide for 16 hours to hydrolyze the -SO2F groups in the polymer (S'-1) and convert them to -SO3K groups. The membrane was then immersed in a 3 mol / L aqueous hydrochloric acid solution for 2 hours. The aqueous hydrochloric acid solution was replaced, and the same treatment was repeated four more times to convert the -SO3K groups in the polymer to sulfonic acid groups, yielding a membrane-like polymer (S-1). The polymer (S-1) was dispersed in a solvent of water / ethanol=50 / 50 (mass %) to obtain a dispersion having a solid content concentration of 13% (hereinafter, also referred to as "dispersion Y1").
[0113] Next, a porous body 1 (manufactured by Donaldson Company, product name "Tetratex II 3108", thickness: 20 μm, average pore size: 3 μm, expanded porous PTFE film) was impregnated with the dispersion Y1 to obtain a solid polymer electrolyte membrane 1 of 20 μm.
[0114] [Solid polymer electrolyte membrane 2] (Synthesis of Compound 2-1) A 2L four-neck flask equipped with a stirrer, condenser, thermometer, and dropping funnel was charged with 560 g of chlorosulfonic acid under a nitrogen gas blanket. The flask was cooled in an ice bath, and a mixture of 139.5 g of compound 1-1 and 478.7 g of dichloromethane was added dropwise over 20 minutes while maintaining the internal temperature at 20°C or less. Heat generation and gas generation were observed during the dropwise addition. After the dropwise addition was completed, the flask was placed in an oil bath, and the reaction was carried out for 7 hours while maintaining the internal temperature at 30-40°C. The reaction proceeded with the generation of gas, and a white solid precipitated. After the reaction, the flask was depressurized and the dichloromethane was distilled off. A yellowish white solid remained in the flask. The solid was 1 H-NMR analysis confirmed that compound 2-1 was produced.
[0115] [ka]
[0116] NMR spectrum of compound 2-1; 1 H-NMR (solvent: D2O): 4.27ppm (-CH2-, 4H, s). 13 C-NMR (solvent: DO): 62.6 ppm (-CH-), 195.3 ppm (C=O).
[0117] (Synthesis of Compound 3-1) Compound 2-1 obtained in Example 1-1 was used as it is in the next reaction without isolation. 2049 g of thionyl chloride was added to the flask of Example 1-1. The flask was heated to 80°C and refluxed for 15 hours. As the reaction proceeded, the reflux temperature rose from 52°C to 72°C. Gas generation was confirmed during the reaction. The reaction was terminated when all of compound 2-1 was dissolved and gas generation ceased. The reaction liquid was transferred to a 2L separable flask and allowed to cool for 9 hours while sealing the gas phase with nitrogen gas, and a black-brown solid precipitated in the separable flask. Unreacted thionyl chloride was removed by decantation. Toluene was added to wash the precipitated solid, and toluene was removed again by decantation. Toluene washing was performed a total of three times, and the total amount of toluene used was 1207 g. The precipitated solid was dried under a nitrogen gas stream at 25°C for 71 hours. The dried solid was collected, 1 Analysis by H-NMR confirmed that 356.5 g of compound 3-1 with a purity of 96.2% was obtained. The yield based on compound 1-1 was 56.0%.
[0118] [ka]
[0119] NMR spectrum of compound 3-1; 1 H-NMR: 5.20ppm (-CH2-, 4H, s). 13 C-NMR: 72.3ppm(-CH2-), 184.6ppm(C=O).
[0120] (Synthesis of Compound 4-1) In a 1L four-neck flask equipped with a stirrer, condenser, and thermometer, 90.0 g of compound 3-1 and 750 mL of acetonitrile were charged under nitrogen gas blanket. The flask was cooled in an ice bath, and 110.3 g of potassium hydrogen fluoride was added while stirring. The heat generated by the addition was slight. The ice bath was replaced with a water bath, and the reaction was carried out for 62 hours while maintaining the internal temperature at 15 to 25 ° C. Fine white solids were produced during the reaction. The reaction liquid was transferred to a pressure filter, and unreacted potassium hydrogen fluoride and the product were filtered off. Acetonitrile was added to the filter, and the filtered solid was washed until the filtrate became transparent, and the washing liquid was collected. The filtrate and washing liquid were put into an evaporator to distill off acetonitrile. 950 mL of toluene was added to the solid remaining after drying, and the solid was dissolved in toluene by heating to 100 ° C. The solution was naturally filtered to remove undissolved matter. The filtrate was transferred to a 1 L separable flask and allowed to cool for 14 hours while sealing the gas phase with nitrogen gas. Light brown needle-like crystals were precipitated in the separable flask. The crystals were washed with toluene and dried at 25°C for 30 hours under a nitrogen gas stream. The dried solid was collected. 1 H-NMR and 19 F-NMR analysis confirmed that 58.1 g of compound 4-1 with a purity of 97.6% was obtained. The yield based on compound 3-1 was 72.3%.
[0121] [ka]
[0122] NMR spectrum of compound 4-1; 1 H-NMR: 4.97ppm (-CH2-, 4H, d, J=3.1Hz). 19 F-NMR: 62.4ppm (-SO2F, 2F, t, J=3.1Hz). 13 C-NMR: 60.7ppm(-CH2-), 184.9ppm(C=O).
[0123] (Synthesis of Compound 5-1) A 200 mL nickel autoclave was charged with 9.93 g of compound 4-1 and 89.7 g of acetonitrile. The autoclave was cooled, and while maintaining the internal temperature at 0 to 5°C, nitrogen gas was fed at a flow rate of 6.7 L / hr to bubble the reaction liquid for 1 hour. While maintaining the temperature of the reaction liquid at 0 to 5°C, a mixed gas of fluorine gas and nitrogen gas (mixing ratio = 10.3 mol% / 89.7 mol%) was introduced at a flow rate of 6.7 L / hr over 6 hours. Nitrogen gas was again fed at a flow rate of 6.7 L / hr to bubble the reaction liquid for 1 hour. 103.2 g of the reaction liquid was recovered from the autoclave. The reaction liquid was 19 Quantitative analysis by F-NMR confirmed that the compound 5-1 was contained in an amount of 8.4 mass %, and the reaction yield based on compound 4-1 was 66%.
[0124] [ka]
[0125] NMR spectrum of compound 5-1; 19 F-NMR: -104.1ppm (-CF2-, 4F, s), 45.8ppm (-SO2F, 2F, s).
[0126] (Synthesis of monomer (m41-1)) A 50 mL four-neck flask equipped with a stirrer, condenser, thermometer, and dropping funnel was charged with 1.65 g of potassium fluoride and 7.8 mL of diethylene glycol dimethyl ether (diglyme). The flask was cooled in an ice bath, and 8.43 g of the reaction solution obtained by the synthesis of compound 5-1 was dropped using a plastic syringe while stirring and maintaining the internal temperature at 0 to 10 ° C. Strong heat generation was confirmed, and the dropping took 15 minutes. After the dropping was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 15 to 20 ° C for 1 hour. The reaction solution was cooled again in an ice bath, and 6.56 g of compound 6-1 was dropped from the dropping funnel while maintaining the temperature of the reaction solution at 0 to 10 ° C. After the dropping was completed, the ice bath was replaced with a water bath, and the reaction was carried out at 20 to 25 ° C for 3.5 hours. The by-product solid was removed from the reaction solution by suction filtration, and the filtrate was collected. The filtration residue solid was washed with an appropriate amount of acetonitrile, and the washing liquid was mixed with the filtrate. 37.1 g of the filtrate19 Quantitative analysis by F-NMR confirmed that the monomer (m41-1) was contained at 2.04 mass%. The reaction yield based on compound 4-1 was 46.6%.
[0127] [ka]
[0128] NMR spectrum of monomer (m41-1); 19 F-NMR: -191.5ppm (CF2=CF-, 1F, ddt, J=116, 38, 14Hz), -133.8ppm (-O-CF-, 1F, tt, J=21.3, 6.1Hz), -103.1ppm (-CF2-SO2F, 4F, m), -101. 5ppm (CF2=CF-, 1F, ddt, J=116, 49, 27Hz), -87.6ppm (CF2=CF-, 1F, ddt, J=49, 38, 7Hz), -67.5ppm (-CF2-O-, 2F, m), 46.8ppm (-SO2F, 2F, s).
[0129] (Synthesis of Polymer (S'-2)) 82.0g of monomer (m41-1) was placed in an autoclave (capacity 100mL, stainless steel), cooled with liquid nitrogen, and degassed. The inside temperature was heated in an oil bath until it reached 100°C. The pressure at this time was 0.25MPaG (gauge pressure). A mixture of 42.3mg of polymerization initiator ((CF3)3COOC(CF3)3) and 4.18g of solvent (CF3(CF2)5H) was pressurized into the autoclave. Nitrogen gas was further introduced from the pressurization line, and the pressurized liquid in the pressurization line was completely pushed in. This operation diluted the TFE in the gas phase, and the pressure increased to 0.49MPaG. TFE was continuously added while maintaining the pressure at 0.49MPaG to carry out polymerization. When the amount of TFE added reached 6.49g after 10.0 hours, the autoclave was cooled to stop the polymerization, and the gas in the system was purged. After diluting the reaction solution with a solvent (CF3(CF2)5H), a solvent (CF3CH2OCF2CF2H) was added to coagulate the polymer and filter it. The polymer was then stirred in the solvent (CF3(CF2)5H) and re-coagulated with the solvent (CF3CH2OCF2CF2H), and this operation was repeated twice. The polymer was dried in a vacuum at 120°C to obtain polymer (S'-2), which is a copolymer of TFE and monomer (m41-1). In the polymer (S'-2), the content of units based on the monomer (m41-1) was 14.1 mol % based on all units contained in the polymer (S'-2). The polymer (S'-2) had a TQ value of 314°C and a glass transition temperature (Tg) of 39°C. The ion exchange capacity of the polymer (S'-2) means the ion exchange capacity of the polymer after hydrolysis treatment as follows. First, the membrane of the polymer (S'-2) described below was vacuum dried at 120°C for 12 hours. Then, the mass of the polymer membrane after drying was measured, and the polymer membrane was immersed in a 0.85 mol / g sodium hydroxide solution (solvent: water / methanol = 10 / 90 (mass ratio)) at 60°C for 72 hours or more for hydrolysis. In this way, a polymer (S-2) was obtained in which the precursor group of the polymer (S'-2) was converted to a sulfonic acid group. The ion exchange capacity of the polymer (S-2) measured by the above-mentioned method was 1.90 meq / g dry resin.
[0130] (Production of solid polymer electrolyte membrane 2) The polymer (S-2) was dispersed in a solvent of water / ethanol = 37 / 63 (mass %) at a solid content concentration of 11% (hereinafter also referred to as "dispersion Y2"), and the above-mentioned porous body 1 was impregnated with the dispersion to obtain a solid polymer electrolyte membrane 2 having a thickness of 20 μm.
[0131] [Solid polymer electrolyte membrane 3] Without using the porous body 1, the dispersion Y1 was used to produce a solid polymer electrolyte membrane 3 having a thickness of 20 μm by a casting method.
[0132] [Example 1] A solution for forming an anode catalyst layer was applied to one surface of the solid polymer electrolyte membrane 1 using a bar coater, dried at 80°C for 10 minutes, and further subjected to heat treatment at 150°C for 15 minutes to obtain a platinum content of 0.1 mg / cm 2 Thus, an electrolyte membrane with an anode catalyst layer was obtained. Next, the cathode catalyst ink was applied onto the ETFE sheet using a die coater, dried at 80°C, and then heat-treated at 150°C for 15 minutes to reduce the platinum content to 0.1 mg / cm. 2 Thus, a cathode catalyst layer decal of 1000 nm was obtained. The surface of the electrolyte membrane with anode catalyst layer on which the anode catalyst layer was not formed was placed opposite the surface of the cathode catalyst layer decal on which the catalyst layer was present, and the electrolyte membrane with anode catalyst layer was bonded to the cathode catalyst layer by hot pressing under conditions of a pressing temperature of 150°C, a pressing time of 2 minutes, and a pressure of 3 MPa. The temperature was then lowered to 70°C, and the pressure was released and the assembly was taken out. The ETFE sheet of the cathode catalyst layer decal was peeled off, and the electrode surface area was set to 25 cm. 2 The membrane electrode assembly of Example 1 was obtained.
[0133] [Example 2] A membrane / electrode assembly of Example 2 was obtained in the same manner as in Example 1, except that the solid polymer electrolyte membrane 2 was used instead of the solid polymer electrolyte membrane 1.
[0134] [Example 3] A membrane / electrode assembly of Example 3 was obtained in the same manner as in Example 1, except that the solid polymer electrolyte membrane 3 was used instead of the solid polymer electrolyte membrane 1.
[0135] [Evaluation test] <Cracks in the cathode catalyst layer> A wet-wet-dry cycle test was carried out by the following method in accordance with the method described in Yeh-Hung Lai, Cortney K. Mittelsteadt, Craig S. Gittleman, David A. Dillard, “VISCOELASTIC STRESS MODEL AND MECHANICAL CHARACTERIZATION OF PERFLUOROSULFONIC ACID (PFSA) POLYMER ELECTROLYTE MEMBRANES”, Proceedings of FUELCELL2005, Third International Conference on Fuel Cell Science, Engineering and Technology, FUELCELL2005, (2005), 74120. The membrane electrode assemblies obtained in each example were used as power generation cells (electrode area 25 cm 2 The cell was installed in a refrigerant cell, and nitrogen gas was supplied to the anode and cathode at a rate of 1 L / min at a cell temperature of 80° C. Nitrogen gas was supplied to the anode and cathode at a rate of 1 L / min. One cycle consisted of supplying nitrogen gas at a humidity of 150% RH for 2 minutes, followed by supplying nitrogen gas at a humidity of 0% RH for 2 minutes. This cycle was repeated. After 10,000 cycles, the presence or absence of cracks in the cathode catalyst layer of the membrane electrode assembly was confirmed using a digital microscope (Keyence VHX-5000) and evaluated according to the following criteria. The evaluation results are shown in Table 1. ○: Observe 6 fields of view at 300x magnification, and the cracks occupy less than 10% of the area ×: When observing six fields of view at a magnification of 300x, the cracks account for 10% or more of the area.
[0136] [Table 1]
[0137] As shown in Table 1, it was confirmed that when the proton-conducting polymer contained in at least one of the catalyst layers of the anode and the cathode has a unit containing a cyclic ether structure and has a sulfonic acid type functional group, by using a solid polymer electrolyte membrane containing a porous body containing a fluoropolymer and a fluoropolymer having a sulfonic acid type functional group, cracking of the catalyst layer in the membrane electrode assembly can be suppressed (Examples 1 and 2). [Explanation of symbols]
[0138] 10 Membrane electrode assembly 11 Catalyst layer 12 Gas diffusion layer 13 Anode 14 Cathode 15 Solid polymer electrolyte membrane
[0139] The entire contents of the specification, claims, drawings and abstract of Japanese Patent Application No. 2019-046159, filed on March 13, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention.
Claims
1. A membrane electrode assembly comprising: an anode having a catalyst layer containing a proton-conducting polymer and a catalyst; a cathode having a catalyst layer containing a proton-conducting polymer and a catalyst; and a solid polymer electrolyte membrane disposed between the anode and the cathode, the proton-conducting polymer contained in the catalyst layer of at least one of the anode and the cathode is a polymer (H) having a unit containing a cyclic ether structure and having a sulfonic acid type functional group, The unit containing a cyclic ether structure contains at least one unit selected from the group consisting of units represented by formula (u12) and units represented by formula (u22), the content of the unit having a cyclic ether structure is 30 mol % or more based on the total units contained in the polymer (H), The ion exchange capacity of the polymer (H) is 0.9 to 1.8 meq / g dry resin; the solid polymer electrolyte membrane comprises a porous body containing a fluoropolymer and a fluoropolymer (S) having a sulfonic acid type functional group, the fluoropolymer (S) has at least one unit selected from the group consisting of units represented by formula (u31), units represented by formula (u32) and units represented by formula (u41), A membrane / electrode assembly, characterized in that the ion exchange capacity of the fluoropolymer (S) is 0.9 to 2.5 milliequivalents / g dry resin. 【Chemistry 1】 In formula (u12), R 21 is a perfluoroalkylene group having 1 to 6 carbon atoms or a perfluoroalkylene group having 2 to 6 carbon atoms and having an ether-bonding oxygen atom between the carbon-carbon bond, R 22 is a fluorine atom, a perfluoroalkyl group having 1 to 6 carbon atoms, a perfluoroalkyl group having 2 to 6 carbon atoms and having an ether-bonding oxygen atom between the carbon-carbon bond, or a group represented by -R 21 (SO 2 X(SO 2 R f ) a ) - M + . M + is H + , a monovalent metal cation, or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group, R f is a linear or branched perfluoroalkyl group which may have an ether-bonding oxygen atom, X is an oxygen atom, a nitrogen atom, or a carbon atom, where a=0 when X is an oxygen atom, a=1 when X is a nitrogen atom, and a=2 when X is a carbon atom. In formula (u22), s is 0 or 1; R 51 and R 52 each independently represent a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a spiro ring formed by linking together (when s is 0); R 53 and R 54 each independently represent a fluorine atom or a perfluoroalkyl group having 1 to 5 carbon atoms; and R 55 is a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. 【Chemistry 2】 In formula (u31), Z is a fluorine atom or a trifluoromethyl group, q is 0 or 1, m is an integer from 0 to 3, p is 0 or 1, n is an integer from 1 to 12, and m+p>0. M + is H + , a monovalent metal cation, or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group. In formula (u32), Q 1 is a perfluoroalkylene group that may have an ether bond oxygen atom, Q 2 is a single bond or a perfluoroalkylene group that may have an ether bond oxygen atom, Y is a fluorine atom or a monovalent perfluoro organic group, q is 0 or 1, R f is a linear or branched perfluoroalkyl group that may have an ether bond oxygen atom, X is an oxygen atom, a nitrogen atom or a carbon atom, and when X is an oxygen atom, a of (SO 2 R f ) a bonded to X is 0, when X is a nitrogen atom, a of (SO 2 R f ) a bonded to X is 1, and when X is a carbon atom, a of (SO 2 R f ) a bonded to X is 2. When two or more R f , a and X are included, two or more R f , a and X may be the same or different from each other. In formula (u41), R F1 and R F2 are each independently a perfluoroalkylene group having 1 to 3 carbon atoms, and Z + is H + , a monovalent metal cation, or an ammonium ion in which one or more hydrogen atoms may be substituted with a hydrocarbon group. The two Z + may be the same or different.
2. 2. The membrane electrode assembly according to claim 1, wherein the porous body is in the form of a woven fabric, a nonwoven fabric, a foam or a film.
3. 3. The membrane / electrode assembly according to claim 1, wherein the fluorine-containing polymer contained in the porous body is at least one selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, and tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer.
4. 4. The membrane / electrode assembly according to claim 1, wherein the porous body has an average pore size of 0.01 to 500 μm.
5. 5. The membrane / electrode assembly according to claim 1, wherein the porous body has an average thickness of 1 to 300 μm.
6. The membrane electrode assembly according to any one of claims 1 to 5, wherein the polymer (H) has a unit based on a perfluoromonomer and / or a unit based on tetrafluoroethylene (TFE).
7. The membrane electrode assembly according to any one of claims 1 to 6, wherein the polymer (S) has units based on a perfluoromonomer and / or units based on tetrafluoroethylene (TFE).
8. The membrane / electrode assembly according to any one of claims 1 to 7, which is used in a polymer electrolyte fuel cell.
Citation Information
Patent Citations
Impregnated film and its manufacturing method
JP2003272664A
Reinforced electrolyte membrane for fuel cell, membrane-electrode assembly for fuel cell, and solid polymer fuel cell with the same
JP2009152215A
Polymer electrolyte membrane
JP2015128060A
Electrolyte material, liquid composition, and membrane-electrode assembly for solid polymer fuel cell
WO2016104380A1